Neurophysiological signatures of hand motor response to dual-transcranial direct current stimulation in subacute stroke: a TMS and MEG study - Kuo, I-J; Tang, C-W; Tsai, Y-A; Tang, S-C; Lin, C-J; Hsu, S-P; Liang, W-K; Juan, C-H; Zich, C; Stagg, CJ; Lee, I-H (BMC, 2020)
Background Dual transcranial direct current stimulation (tDCS) to the bilateral primary motor cortices (M1s) has potential benefits in chronic stroke, but its effects in subacute stroke, when behavioural effects might be expected to be greater, have been relatively unexplored. Here, we examined the neurophysiological effects and the factors influencing responsiveness of dual-tDCS in subacute stroke survivors.